2019
DOI: 10.7150/jca.32281
|View full text |Cite
|
Sign up to set email alerts
|

Centromere Protein N Participates in Cellular Proliferation of Human Oral Cancer by Cell-Cycle Enhancement

Abstract: Centromere protein N (CENP-N), an important member of the centromere protein family, is essential for kinetochore assembly and chromosome segregation; however, the relevance of CENP-N in cancers remains unknown. The aim of this study was to investigate CENP-N expression and its functional mechanisms in oral squamous cell carcinoma (OSCC). CENP-N expression was up-regulated significantly in vitro and in vivo in OSCCs. Overexpressed CENP-N was closely (p < 0.05) corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 34 publications
2
21
1
Order By: Relevance
“… Rahman et al (2019) identified CENPN as a poor prognostic marker for colorectal cancer by bioinformatics analysis. Recently, it was reported that CENPN can promote the proliferation of oral cancer cells in the entrance cavity by regulating the cell cycle ( Oka et al, 2019 ). However, the expression of CENPN in HCC and its role and mechanism in malignant development are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Rahman et al (2019) identified CENPN as a poor prognostic marker for colorectal cancer by bioinformatics analysis. Recently, it was reported that CENPN can promote the proliferation of oral cancer cells in the entrance cavity by regulating the cell cycle ( Oka et al, 2019 ). However, the expression of CENPN in HCC and its role and mechanism in malignant development are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation of these complexes results in other proteins not being phosphorylated, including pRb (RB1), so it is unable to release E2F transcription factors to activate the expression of genes that regulate S phase (Matsuoka et al, 1994). Previous research has revealed that the negative regulation of cyclin D1 and CDK4 is consistent with the downregulation of CENPN (Molenaar et al, 2008), and recent reports in oral squamous cell carcinoma (OSCC) suggest that downregulation of CENPN can reduce the expression of cyclin D1 and CDK4 with corresponding increases in the expression of p21 and p27 (Oka et al, 2019). This suggests that interfering with CENPN expression in OSCC can upregulate p27 and p21 expression to inhibit CDK4 and cyclin D1 expression and arrest the cell cycle in G1 phase.…”
Section: Discussionmentioning
confidence: 99%
“…(22) As previous studies reported, other Centrome protein such as CENPN knockdown (shCENP-N) cells showed depressed cellular proliferation by cell-cycle arrest at the G1 phase with up-regulation of p21Cip1 and p27Kip1 and down-regulation of cyclin D1, CDK2, and CDK4. (23) The mechanism of CENPO in cancer was insu cient, our research rstly demonstrated that CENPO may affect apoptosis related protein, cell cycle related proteins and PI3K/AKT/mTOR signaling thus regulated many malignant behaviors such as proliferation, apoptosis, cellcycle thus promoting the progression of NSCLC. However, whether these relationship had connected relationship or cross taking.…”
Section: Discussionmentioning
confidence: 89%
“…CENP-N plays an essential role in cell cycle progression and cell mitosis [33,41]. Localization of CENP-N in different cell phases and incorrect congression and segregation of chromosomes by depletion of CENP-N in silkworms have uncovered its kinetochore function.…”
Section: Discussionmentioning
confidence: 99%